Environmental Literacy in Science Education: A Systematic Literature Review of Conceptual Emphases, Instructional Resources, and Methodological Trends - Ahmad Saputra; Insih Wilujeng; Antuni Wiyarsi (Universitas Pendidikan Mandalika, 2026)
The increasing complexity of environmental issues highlights the importance of environmental literacy as a key competence within science education; however, existing research remains fragmented in terms of conceptual emphases, instructional resources, and methodological practices. This study systematically examines research trends on environmental literacy in science education, focusing on investigated dimensions, learning materials and resources, methodological approaches, and data collection instruments. A systematic review was conducted following the PRISMA 2020 guidelines. Articles were retrieved from the Scopus database and screened through identification, screening, and eligibility stages, resulting in twenty-one peer-reviewed studies published between 2016 and 2025. The findings indicate that environmental literacy is predominantly conceptualized as a multidimensional construct encompassing cognitive, affective, and behavioral components, with a strong emphasis on cognitive aspects, particularly environmental knowledge and conceptual understanding. Experiential and technology-enhanced learning resources are most frequently employed, while traditional textbook-based materials are less common. Methodologically, quantitative approaches and questionnaire-based instruments dominate the field. Overall, this review reveals persistent conceptual and methodological imbalances and highlights the need for more integrated frameworks and diverse research approaches to support meaningful environmental literacy development through science education.